Racial attitudes and Asian Pacific Americans demystifying the model minority - Inkelas, Karen Kurotsuchi (Studies in Asian Americans, 2006)
Examines the complex sources and implications of the racial attitudes of Asian Pacific American (APA) college students, who, as one of the fastest growing demographics in higher education enrollments, play an increasingly significant role in campus race relations.